Analisis Faktor-Faktor Yang Mempengaruhi Efektivtas Kelompok Tani Kopi Arabika Di Kecamatan Sangir Kabupaten Solok Selatan - Joni Pardilo; Asmawi; Zulvera (Jurnal Niara, 2020)
ABSTRACT The purpose of this study was to determine 1) How far the level of effectiveness of Arabica coffee farmer groups in Sangir Subdistrict, South Solok Regency. 2) How far the influence of internal factors on the effectiveness of Arabica coffee farmer groups in Sangir Subdistrict, South Solok Regency. 3) How far the influence of external factors on the effectiveness of Arabica coffee farmer groups in Sangir Subdistrict, South Solok Regency. The population in this study are farmers who are members of farmer groups who are trying to grow Arabica coffee in Sangir District, where there are 10 (ten) farmer groups with 166 members. Samples were calculated using the slovins formula with a total of 117 people. Sampling in the population using a multistage sampling technique, while to determine the number of research samples in each farmer group using proportional random sampling method. Analysis of the data used in this study is quantitative descriptive analysis and multiple linear regression analysis. Based on the results of the analysis and discussion, a number of conclusions can be made as follows 1) The effectiveness of the Arabica coffee farmer groups in Sangir Selatan, Solok Selatan sub-district can be seen from the first group productivity, which is carried out effectively enough so that it appears that members of the farmer groups are mutually help its members to grow their farming business. Second, member satisfaction, as a whole is carried out effectively enough so that it appears that members of the farmer group can enjoy their respective roles as group members and the role and function of the group in supporting needs and solving problems in trying to farm coffee. Based on the results of the analysis, it was found that the internal factors of the group had a positive and significant effect on the effectiveness of the Arabica coffee farmer group in Sangir Subdistrict, South Solok Regency. Keywords: Internal Group Factors, Group External Factors, Group Effectiveness ABSTRAK Tujuan penelitian ini untuk mengetahui 1) Sejauhmana tingkat efektivitas kelompok tani kopi Arabika di Kecamatan Sangir Kabupaten Solok Selatan. 2) Sejauhmana pengaruh faktor internal terhadap efektivitas kelompok tani kopi Arabika di Kecamatan Sangir Kabupaten Solok Selatan. 3) Sejauhmana pengaruh faktor eksternal terhadap efektivitas kelompok tani kopi Arabika di Kecamatan Sangir Kabupaten Solok Selatan. Populasi dalam penelitian ini adalah petani yang menjadi anggota kelompok tani yang berusaha tani kopi Arabika di Kecamatan Sangir, dimana kelompok taninya yaitu sebanyak 10 (sepuluh) kelompok tani dengan anggota sebanyak 166 orang petani. Sampel dihitung menggunakan rumus slovins dengan jumlah sebanyak 117 orang. Penarikan sampel dalam populasi menggunakan teknik penarikan sampel bertahap (multistage sampling), sedangkan untuk menentukan jumlah sampel penelitian pada masing-masing kelompok tani dengan menggunakan metode proporsional random sampling. Analisis data yang digunakan pada penelitian ini adalah analisis deskriptif kuantitatif dan Analisis regresi linier berganda. Berdasarkan hasil analisis dan pembahasan, maka dapat dibuat beberapa kesimpulan sebagai berikut 1) Gingkat efektivitas kelompok tani kopi kopi arabika di kecamatan sangir kabupaten solok selatan dapat dilihat dari petama produktvitas kelompok, dimana secara kesleuruhan dilaksanakan dengan cukup efektif sehingga terlihat bahwa anggota kelompok tani tersebut saling membantu anggotanya agar usaha taninya berkembang. Kedua Kepuasan anggota, secara keseluruhan dilaksanakan dengan cukup efektif sehingga terlihat bahwa anggota kelompok tani tersebut dapat menikmati peran mereka masing-masing sebagai anggota kelompok maupun peran dan fungsi kelompok dalam menunjang kebutuhan serta menyelesaikan masalah dalam berusaha tani kopi. Berdasarkan hasil analisis ditemukan faktor internal kelompok berpengaruh positif dan signifikan terhadap efektivitas kelompok tani kopi arabika di Kecamatan Sangir Kabupaten Solok Selatan. Kata Kunci : Faktor Internal Kelompok, Faktor Eksternal Kelompok, Efektivitas Kelompok